The Incentive Effects of Dismissals, Efficiency Wages, Piece-Rates and Profit-Sharing - Kraft, Kornelius (The Review of Economics and Statistics, 1991)
The relation of several incentive schemes to productivity is studied, with a particular emphasis on the effects and determinants of dismissals. Dismissals turn out to be positively, but in a nonlinear way, associated with productivity. Similarly, profit-sharing raises productivity. Wages and piece-rates are insignificant. Profit-sharing decreases the number of dismissals made by firms. Copyright 1991 by MIT Press.